STRUCTURE DYNAMIC CHARACTER OPTIMIZATION AT THERMAL ENVIRONMENT - XUE HongJun; ZHANG Yong; ZHANG XiaoYan (Jixie qiangdu)
Many aircraft structures are in thermal and vibration composite environment,and the two both should be taken into account in structural optimization design. Thermal environment influences the structural dynamic characteristics on the change of structural stiffness matrix,and then changes of the structure natural frequency. Basing on the analysis of structural dynamics in thermal environment optimization model was built both for uniform temperature field and thermal conduction structure Considering the manufacture process, the model optimizes the dynamic characteristics of structure. Results suggest that optimization considering the thermal environment of structural dynamics characteristics can improve the structure natural frequency and then keep the natural frequency away from the range of external excitation frequency to avoid resonance phenomenon caused by the change of the structural natural frequency resulting in thermal environment.